2017 European Conference on Networks and Communications (EuCNC) 2017
DOI: 10.1109/eucnc.2017.7980726
|View full text |Cite
|
Sign up to set email alerts
|

Beyond WYSIWYG: Sharing contextual sensing data through mmWave V2V communications

Abstract: Abstract-In vehicular scenarios context awareness is a key enabler for road safety. However, the amount of contextual information that can be collected by a vehicle is stringently limited by the sensor technology itself (e.g., line-of-sight, coverage, weather robustness) and by the low bandwidths offered by current wireless vehicular technologies such as DSRC/802.11p. Motivated by the upsurge of research around millimeter-wave vehicle-to-anything (V2X) communications, in this work we propose a distributed vehi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…An early work about the use of mmWave to share LIDAR data between vehicles was [108]. This paper proposed a distributed algorithm for communication link allocation between vehicles, and concluded that it is important to consider not only link information (distance for example) but also the value of the information exchanged (receiving information from two nearby vehicles may cause resources to be expended in obtaining redundant information).…”
Section: V2v Bi-directional Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…An early work about the use of mmWave to share LIDAR data between vehicles was [108]. This paper proposed a distributed algorithm for communication link allocation between vehicles, and concluded that it is important to consider not only link information (distance for example) but also the value of the information exchanged (receiving information from two nearby vehicles may cause resources to be expended in obtaining redundant information).…”
Section: V2v Bi-directional Communicationmentioning
confidence: 99%
“…Distributed direct communication link allocation [108] Network-based resource allocation in PC5 interface [135] [136] V2V communications through the Uu interface [110] Demonstration/analysis of specific applications [108] [110] [103] Performance evaluation tested with real-life equipment [110] [103]…”
Section: Contributions Related Papersmentioning
confidence: 99%
“…The use of Matching Theory [27] -a mathematical framework from labor economics that attempts to describe the formation of mutually beneficial relationships over time-, has recently garnered a considerable interest in the context of resource allocation for wireless networks [28] with applications as varied as V2V communications [29], [30], FD-NOMA/OMA [31] or Fog computing [32]. However, for the sake of completeness we will first provide several definitions to properly address the fundamentals of this framework adapted to the problem at hand.…”
Section: Schedulingmentioning
confidence: 99%
“…However, autonomous vehicle systems relying solely on ego-vehicle sensors have limitations in dealing with the collisions due to reasons such as bad weather, sensor malfunctioning, or blind spots, etc. [7][8][9]. The risk can be reduced by utilizing sensed information from the neighboring vehicles through Vehicle-to-Vehicle (V2V) communication [10,11] such as Dedicated Short Range Communications (DSRC) [12] which can support safety applications in high data rates [13,14].…”
Section: Introductionmentioning
confidence: 99%